2008
DOI: 10.1145/1452335.1452341
|View full text |Cite
|
Sign up to set email alerts
|

A day at the root of the internet

Abstract: We analyzed the largest simultaneous collection of full-payload packet traces from a core component of the global Internet infrastructure ever made available to academic researchers. Our dataset consists of three large samples of global DNS traffic collected during three annual "Day in the Life of the Internet" (DITL) experiments . Building on our previous comparison of DITL DITL 2007 DNS datasets [28], we venture to extract historical trends, comparisons with other data sources, and interpretations, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 14 publications
2
70
0
8
Order By: Relevance
“…Similar to our previous analyses [23,7], we categorized DNS root pollution into nine groups i.e. (i) unused query class; (ii) A-for-A queries; (iii) invalid TLD; (iv) non-printable characters; (v) queries with ' '; (vi) RFC 1918 PTR [15]; (vii) identical queries; (viii) repeated queries; and (ix) referral-not-cached queries.…”
Section: Trends In Dns Workload Characteristicssupporting
confidence: 89%
See 3 more Smart Citations
“…Similar to our previous analyses [23,7], we categorized DNS root pollution into nine groups i.e. (i) unused query class; (ii) A-for-A queries; (iii) invalid TLD; (iv) non-printable characters; (v) queries with ' '; (vi) RFC 1918 PTR [15]; (vii) identical queries; (viii) repeated queries; and (ix) referral-not-cached queries.…”
Section: Trends In Dns Workload Characteristicssupporting
confidence: 89%
“…In theory, a caching recursive nameserver only needs to query the root nameservers for an unknown top level domain or when a TTL expires. However, many previous studies have shown that the root nameservers receive many more queries than they should [23,22,13,7]. Figure 5 shows the distributions of clients and queries binned by average query rate order of magnitude, ranging from 0.001 q/s (queries per second) to >10 q/s.…”
Section: Trends In Dns Workload Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have examined DNS traffic measurement techniques and performance metrics [8,21,24]. However, hardly any research has examined DNS health in relation to the prescribed indicators.…”
Section: Stabilitymentioning
confidence: 99%